Frequency and Clinical Outcomes of Respiratory Infections in Children with Cancer Presenting with Febrile Illness - Srinivasan, Arathi; Sekar, Ramya Manur; Chandy, Sara; Sundaram, Balasubramanian (South Asian Journal of Cancer, 2024)
Objectives Fever is a known complication in pediatric cancer patients when on chemotherapy for which prompt initiation of empiric antibiotics is the single most important life-saving intervention. Nearly two-thirds of all children are treated without identifying the source of fever. Molecular diagnostics can improve management of febrile episodes and reduce unnecessary antibiotic use. The purpose of our study was to evaluate the pathogenic etiology of febrile episodes and analyze their clinical characteristics.Materials and Methods We conducted a prospective observational study at our tertiary care institution from January 2019 to March 2020, to identify the etiology of febrile episodes with or without neutropenia in pediatric cancer patients and to study their clinical outcomes.Results Forty febrile episodes were observed among 27 patients over a period of 15 months. The mean age group was 5 years. In 28 febrile episodes without a focus (70%), a respiratory organism (virus, bacteria, or coinfection) was detected. Rhinovirus was the most common single respiratory isolate (47.36%), followed by Streptococcus pneumoniae (21.05%) and six episodes had multiple viral isolates (21.42%). There was no prolonged hospitalization, need for intensive care unit or oxygen requirement, or mortality. The most common antibiotic used in empiric management was piperacillin–tazobactam. Aminoglycosides were added when there was a clinical suspicion of resistant organism.Conclusion Around 70% of febrile episodes without a focus or documented infection in cancer children had a respiratory pathogen identified in nasopharyngeal swab. Molecular diagnostics greatly enhances diagnostic sensitivity and thereby individualizes the management of febrile illness in these children.
Keywords: pediatric cancer; febrile illness; neutropenia; respiratory virus; bacterial infection